Dampak Pemutusan Hubungan Kerja di Masa Pandemi Covid-19 Terhadap Ketahanan Keluarga (TAWAZUN: Journal of Sharia Economic Law, 2021)
The purpose of this study was to determine the impact of termination of employment during the Covid-19 pandemic on family resilience. This study uses a case approach and a law approach with primary legal sources and secondary legal sources in the form of books or legal journals related to the research title. The results of this study indicate that the termination of employment experienced by the head of the family or family member during the Covid-19 pandemic did not significantly affect family resilience, as evidenced by the divorce rate which did not increase significantly and was not caused by termination of employment. As for maintaining family resilience during the Covid-19 pandemic can be done by carrying out the rights and obligations of each family member in accordance with the study of Islamic family law, in addition to maintaining interpersonal communication between family members.